The Propagation Mechanism of Financial Stress in the Context of Global Crises - YALÇINER, Zeycan; HAZAR, Adalet; BABUŞCU, Şenol (International Journal of Contemporary Economics and Administrative Sciences, 2025)
This study examines the dynamic relationship between the uncertainty indices of various Asian countries and the Kansas City Financial Stress Index (KCFSI) of the United States using cross-wavelet transform analysis and Toda-Yamamoto causality test between the period of 2008:01- 2025:02. The findings reveal significant in-phase coherence, indicating that financial stress in the US often precedes increases in economic uncertainty across Asia, particularly during global crises like the 2008 financial crisis and the COVID-19 pandemic. The results highlight the varying degrees of coherence and lead-lag relationships across countries, reflecting differences in economic structures and integration into global markets. These insights emphasize the need for stronger regional financial cooperation, proactive economic policies, and robust risk management strategies to mitigate the impact of external financial shocks. The study concludes with recommendations for future research, including the exploration of additional factors influencing financial stress transmission and the role of emerging financial technologies in global economic stability.